Mirabegron 50 mg once daily, long-term treatment maximizes benefit in middle-aged and older people with overactive bladder syndrome: a systematic review and meta-analysis of nine phase II/III, randomized, double-blind, parallel-design, placebo-controlled, multicenter, and multinational trials - Zhang, Xiangxiang; Mao, Yinhui; Liu, Yang; Sun, Jilei; Sun, Juntao; Pan, Chenli; Wang, Zhuo; Wei, Zhitao; Yang, Yong (Frontiers in Surgery, 2024)
The prevalence and severity of overactive bladder increase with age, and mirabegron is an approved treatment for this condition. This meta-analysis systematically evaluated the efficacy and safety of mirabegron compared with placebo for overactive bladder treatment. We searched PubMed and the Cochrane Library (30 October 2023) for relevant articles (source: MEDLINE, EMBASE, ClinicalTrials.gov, ICTRP, CINAHL). We included randomized controlled trials involving adults with overactive bladder syndrome that compared mirabegron with placebo treatment. Data were analyzed according to the Cochrane Handbook for Systematic Reviews of Interventions [Review Manager (computer program) Version 5.4]. Nine parallel-group trials (10 articles) were included. The evaluation included a total of 8,527 adults, including 6,445 women and 2,082 men, of whom 5,726 were White, 2,462 were Asian, and 161 were Black. The mean age of the participants ranged from 53.4 to 60.3 years. This evaluation involved three specifications of mirabegron: 25 mg, 50 mg, and 100 mg. In all trials, patients were enrolled in a 12-week double-blind treatment period, and the dose was once daily. The review of trials found that on average, people taking mirabegron had about 13 ml more volume voided per micturition, five fewer micturitions, and four fewer incontinence episodes every week, with moderate improvements in quality of life. About one in five people taking the drug reported TRAEs. Mirabegron treatment is well tolerated, with the risk of adverse events similar to that of a placebo. For best results, a dose of 50 mg once daily is recommended for long-term use. It is unclear whether any benefits are sustained after treatment discontinuation. Systematic Review Registration: https://www.crd.york.ac.uk/prospero/, PROSPERO (CRD42023430737).